Development of a spray dryer’s mathematical model for control tasks - Олексій Володимирович Ситніков; Денис Миколайович Складанний; Костянтин Ігорович Соколов (Вісник Національного технічного університету України «Київський політехнічний інститут імені Ігоря Сікорського»: Серія «Хімічна інженерія, екологія та ресурсозбереження», 2023)
The sustainable development paradigm includes the most efficient material and energy resources using in production processes. One of the ways to achieve this goal is creating the effective automated control systems. At the same time, such systems effective functioning is impossible without adequate mathematical models for control objects. Thus, the actual task of this study is to create the control object – a spray dryer -model-, which could be used in the control system.